English Language Teaching and Globalization: to Support Economic Growth - Dita Adawiyah; Asti Gumartifa (Premise: Journal of English Education and Applied Linguistics, 2022)
The English language is no doubt significant for communication in the international community. It may not be the most widely spoken language globally, but it is the official language in many countries. This paper aims to analyze why the English language plays a significant role in supporting economic growth and the factors that influence the use of the English language in the era of globalization. A function that helps people communicate promotes nation-to-nation development and builds relationships with other countries. The survey design used a survey, the type of survey used a descriptive survey, and the equipment used was student observation. The results show that the economy is becoming increasingly global, and more and more countries are turning to the English language for business reasons. In conclusion, the English language is a significant contributor to sustainable development, so those who do not speak the English language do not stand a chance.